Respuesta :
x= 1, x = 5
-3|x - 3| = -6
———— —– divide both sides by -3
-3 -3 and remove the bars
x - 3 = 2
+3 +3
—————
x = 5⭐️
-3|1-3|➡️-3|-2|= -6
-3|x - 3| = -6
———— —– divide both sides by -3
-3 -3 and remove the bars
x - 3 = 2
+3 +3
—————
x = 5⭐️
-3|1-3|➡️-3|-2|= -6
Answer:
A. x = 1, x = -1
Step-by-step explanation:
Given the inequality
−3|x − 3| = −6
The equation will give us two solutions due to the nodulus sign. The modulus sign means that the function x- 3 can take both positive and negative value.
If |x-3| is positive, we have:
-3(x+3) = -6
-3x-9 = -6
Moving -9 to the other side:
-3x = -6-(-9)
-3x = -6+9
-3x = 3
x = 3/-3
x = -1
Similarly if |x-3| is negative, we have:
-3{-(x-3)} = -6
-3(-x+3) = -6
3x-9 = -6
3x = -6+9
3x = 3
x = 3/3
x = 1
The solutions are x = -1 and x = 1